CO2 Chemisorption Behavior of Coordination‐Derived Phenolate Sorbents. Issue 14 (2nd July 2021) - Suo, Xian; Yang, Zhenzhen; Fu, Yuqing; Do‐Thanh, Chi‐Linh; Chen, Hao; Luo, Huimin; Jiang, De‐en; Mahurin, Shannon M.; Xing, Huabin; Dai, Sheng
Abstract: Invited for this month′s cover is the group of Sheng Dai at the Oak Ridge National Laboratory. The image shows the CO2 chemisorption behavior of coordination‐derived phenolate sorbents. The Communication itself is available at 10.1002/cssc.202100666 . Abstract : "CO2 chemisorption via C−O bond formation is an efficient methodology in carbon capture…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202100666 . View the Front Cover here: 10.1002/cssc.202101256 .